2012
DOI: 10.1186/1756-0500-5-450
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life evaluation in Japanese pregnant women with striae gravidarum: A cross-sectional study

Abstract: BackgroundStriae gravidarum is a physiological skin change that many pregnant women experience during pregnancy. The striae are often accompanied by a reddish purple color during pregnancy, and then lose pigmentation and become atrophic in the long term after pregnancy. Striae gravidarum seems to be undesirable to many pregnant women. However, the impact of striae gravidarum on pregnant women who experience it has not been clarified. The aim of this study was to evaluate the impact of striae gravidarum on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 25 publications
0
90
0
1
Order By: Relevance
“…However, there was no significant difference considering dimensions of function and symptoms and also general life quality between women with and without striae. This discrepancy between the findings might be due to striae prevalence (about 39.1%) (15). One’s impression of skin status is a determining factor in quality of life.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, there was no significant difference considering dimensions of function and symptoms and also general life quality between women with and without striae. This discrepancy between the findings might be due to striae prevalence (about 39.1%) (15). One’s impression of skin status is a determining factor in quality of life.…”
Section: Discussionmentioning
confidence: 89%
“…Al-Himdani et al (2013) suggested that striae leads to reduced quality of life and is a limiting factor in life (14). Yamaguchi et al (2012) showed there was no significant association between striae and general life quality, the dimension of symptoms and functions of skin quality of life index (15). Yamaguchi et al (2014) showed pregnant women with striae had a lower quality of life in the dimension of emotion; the preventive steps were associated with the level of quality of life in the dimension of emotion, in pregnant women with striae (16).…”
Section: Introductionmentioning
confidence: 99%
“…The function subscale consists of questions related to daily life, such as sleep, work, hobbies, social life, staying at home, intimacy issues, between the individual and their partners, sexual dysfunction, living alone, and fatigue. The participants' answers were converted into linear scale scores between 0 (ineffective) and 100 (maximum effect) 79. The higher the scale score (from 0 to 100) indicated a lower QOL 7…”
Section: Methodsmentioning
confidence: 99%
“…WHOQOL-BREF short form is a self-assessment questionnaire consisting of four areas and a total of 26 questions. Twenty-four questions are related to physical health, psychological health, social relationships, and environment, and the remaining two key questions are related to the overall well-being status 91213. The participants' responses range between 1 (never) and 5 (extremely).…”
Section: Methodsmentioning
confidence: 99%
“…cal problem, but can cause psychological distress, due to adverse appearance and physical characteristics such as thickness and suppleness, and is undesirable to those affected [1]. Caused by pregnancy, rapid weight gain or loss, or a growth spurt in the early teens, the physiological cause is reportedly linked to hormonal changes and their consequences in the skin metabolism of the affected area [2].…”
mentioning
confidence: 99%